Building and performing: early 16th-century Portuguese presence in Azammūr - Correia, Jorge (2014)
Azammūr was the last great Portuguese conquest in North Africa (1513-1542). On the one hand, it represented the last stage of a broader strategy of establishment in Morocco still fired by crusade ideology. Christian Azammūr proposed a new urban space, which was celebrated by contemporary Portuguese narratives. Beyond technological, urban and military innovations, the Portuguese presence in Azammūr was affirmed through a symbolic rhetoric that would often surpass the political occupation itself. On the other hand, those in Azammūr faced a harsh reality; the city did not attract numerous Portuguese settlers and the local economy showed few signs of intense activity. Eventually, Azammūr experienced armed confrontations and alliances between its Christian, Muslim and Jewish communities. Methodologically, this study offers an analysis of cross-referenced archaeological, architectural and documentary material. It was carried out as a part of a research project from 2007 to 2011. It presents the first contemporary and updated synthesis of the historical process that led to the ruling and abandonment of Azammūr by the Portuguese, and thus remains relevant to understanding Muslim-Christian relations and exchanges in terms of their military, social and spatial aspects. Moreover, the paper examines the period when Europe evolved from late-medieval conceptions to early-modernity.